2021
DOI: 10.7554/elife.70003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk perception and physician communication behaviors on cervical cancer and colorectal cancer screening

Abstract: Background:Women 50–65 years of age have the lowest cervical and colorectal cancer (CRC) screening rates among ages recommended for screening. The primary aim of this work is to determine how cancer risk perceptions and provider communication behaviors, in addition to known demographic factors, influence the uptake of both cervical and CRC screening or a single screen among women in southeast Michigan.Methods:Fourteen health services and communication behavior questions were adapted from the Health Information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The logistic regression analysis showed that inquiries from dentist (Q5f) were associated with the disclosing behavior, although physician’s advice was distinctively associated with informing the dentist. This result supports the findings of previous studies 13 , 14 that physician’s recommendations motivate patients and are associated with willingness to undergo cancer screening. We revealed that the patient's perception of being recommended by their physicians was a strong motivator for patients’ disclosing behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The logistic regression analysis showed that inquiries from dentist (Q5f) were associated with the disclosing behavior, although physician’s advice was distinctively associated with informing the dentist. This result supports the findings of previous studies 13 , 14 that physician’s recommendations motivate patients and are associated with willingness to undergo cancer screening. We revealed that the patient's perception of being recommended by their physicians was a strong motivator for patients’ disclosing behavior.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, it is not the religion, sex, or culture of the physician that creates the safe environment for a routine physical devoid of religious or cultural overtones, it is the relationship the woman has with her PCP. 17 These insights are powerful observations of the evolution of immigrant cultures seeking necessary health care. Likewise, our insights show that physician behaviors of cultural competency and professional conduct are also necessary for MENA women to receive appropriate healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior studies in this population informed the choice of the covariates that had been significant for predicting other cancer screenings for this study. 6 , 8 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…We developed a community-based survey conducted between May 1- October 28, 2019, among White, Black, and MENA populations in southeast Michigan who were 18 years or older, as described elsewhere ( Harper et al, 2021 , Harper et al, 2021 , Resnicow et al, 2021 ). The primary aim of this survey was to systematically assess the cancer prevention and screening behaviors of these major racial/ethnic subpopulations who reside in the Rogel Cancer Center catchment area.…”
Section: Methodsmentioning
confidence: 99%